CARBON MARKET IN RUSSIA. ORGANIZATIONAL ISSUES - BELIK, Irina; STARODUBETS, Natalia (Journal of Environmental Management and Tourism; Vol 6 No 2 (2015): JEMT Volume VI Issue 2(12) Winter 2015, 2016)
Cap-and-trade system implemented in flexibility mechanisms of Kyoto Protocol and in regulatory carbon markets showed its efficiency in reducing carbon intensity of GDP and pollution of the environment. Russia, together with other countries, such as Ukraine, Kazakhstani etc., has just made the first steps towards carbon market. Therefore, the main purpose of this paper is to bring forward an organizational mechanism of carbon market in Russia. As a result, paper describes a set of actions that should be taken by policymakers at both preparatory and basic stages of carbon market introduction. One of such actions is building up a digital platform for carbon projects at the regional and national levels (The Bank of Carbon Projects) where all projects should be ranked according to the procedures described in the paper. Decision-makers in Russia and other transition countries when creating domestic carbon markets outside the Kyoto Protocol may use obtained results.
Keywords: carbon market; cap-and-trade system; greenhouse gases emission reduction; Bank of Carbon Projects; projects ranking